A comunicação pública da ciência nos portais das universidades federais do nordeste - Costa, Marcilio José de Sousa (2019)
With the objective of diagnosing potential tools to communicate science to the public, this research analyzed the Web portals of the federal universities of the Northeast region, in order to identify the use of resources of the digital technologies provided by the Internet for Public Communication of Science. For this, we conducted an exploratory research on the structure and contents of these institutions' portals, documenting the results in the most possible exhaustive way. The literature needed to base theoretically the research focused on the approaches of Public Communication of Science (CPC) and Mediaization of Science. The empirical research was based on a geographic reading of the conditions of production of science and its public communication, guided by the concept of technical-scientificinformational medium, from the Brazilian geographer Milton Santos, associated to historical data series on undergraduate courses and postgraduate programs in Brazil between the years 1960 and 2015. Upon this, we identified that the conditions of emergence and maintenance of the universities contribute to their performance in research, but not necessarily to the communication of science. Among the 18 federal universities based in the Brazilian Northeast, only five have systematic CPC actions. Practically all the others promote isolated actions, lacking a strategic articulation with the institutional communication. It was also verified that in the majority of these universities actions for scientific dissemination were discontinued with the time. We conclude, then, that institutional factors - such as internal policies and personnel structure - influence the conditions for communicating (or not) science.